Pelatihan Pembuatan Media Ajar Interaktif Berbasis Multimedia Untuk Inovasi Pembelajaran Bagi Guru Sekolah Dasar Islam Az-Zahra Palembang Dengan Camtasia - Ali Ibrahim; Endang Lestari; Fathoni Fathoni; Rizka Dhini Kurnia; Mira Afrina; Ahmad Rifai (Annual Research Seminar (ARS), 2015)
Making training activities based interactive multimedia instructional media for learning innovations for primary school teachers of Islam az-zahra palembang with Camtasia is an activity at the request of the Islamic Primary School Zahra Palembang, through the Head of School for the training was held. This activity aims to share knowledge to teachers in terms of making media-based teaching animation with Camtasia program. Besides the goal is held in order to attract and increase student interest in learning and understanding the material. This training is followed by approximately ± 30 participants were taught in elementary school. Thank God, this training can be run in accordance with the expectations, it can be seen from the enthusiasm of the participants in the training. From the observation and discussion directly during training, it appears that the participants were very pleased training, because in accordance with the opinion of some participants that the use of this method is a very interesting and they are sure to be able to increase student interest. During the training activities, participants easily and can be training because it is supported by the module are clear and detailed, so that participants can easily try and create teaching materials with Camtasia animation program. From the observation team directly approximately 90% of participants declared successful, because participants are able to try themselves at the moment in the given exercise. While 10% of